MasterClass in history education : transforming teaching and learning - Counsell, Christine (MasterClass (Bloomsbury (Firm)), 2016)
MasterClass in History Education draws on international research and practice to present effective and engaging approaches for history teachers who want to explore the ways in which reading, research and reflection can support the development of history teaching and learning in the classroom. At the heart of the book is a series of professional enquiries carried out by experienced history teachers, working in a range of contexts. Each history teacher addresses clear questions arising from their practice and together they illustrate various approaches to data collection, data analysis and argument. These history teachers also show how they drew on diverse scholarship in history and history education, including many publications by other history teachers. In eight further chapters, other experts, ranging from practitioner-scholars to researchers in diverse fields (such as history, history education, teacher education, teacher research and curriculum theory) reflect on the distinctive insights that these teachers offer and explore connections with their own fields. The combination of perspectives and the depth of knowledge of the varied contributors reveal the importance of different kinds of relationship between 'theory' and 'practice.' The links between classroom realities and research and the critical use of different kinds of text will support history teachers in developing their practice and professional voice.